Legal Measures to Expand the Crackdown on Offenders Serious About Drugs According to the Drug Code - Phocharoen, Chatchai (Legal State Journal, 2025)
This research article aims to study the legal problems of measures to expand the evidence of collusion and measures to inspect assets to suppress serious drug offenders in Thailand by studying and comparing drug laws, measures to expand the evidence of collusion and measures to inspect assets to prove the guilt of serious drug offenders in Thailand with other countries. The researcher used qualitative research methods, including documentary research, in-depth interviews with 20 experts, and focus group discussion with 6 people, to improve and amend the Narcotics Code for use in suppressing serious drug offenders. Data were analyzed using content analysis. Findings are as follows: The Narcotics Code of 2021 does not yet have a clear definition of “providing important information in drug cases” that covers the seizure of assets in drug cases, including the determination of procedures for providing important information at the arrest, investigation, and trial stages. There is also no provision requiring officers to adhere to the same guidelines to protect the rights of those arrested, suspects, or defendants so that officers do not neglect to inform them of the law that is beneficial for providing important information to expand the suppression of serious drug offenders.